Meningkatkan Kemampuan Literasi Digital Siswa Sekolah Dasar di Era Digital - Putri Nur Anggraeni; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
This research aims to improve the digital literacy skills of elementary school students in the digital era, which indicates concern for technological developments. Efforts to increase the literacy of elementary school students have become a priority in education. This article discusses the important role of technology in student literacy development, underscoring the need for students to not only be fluent in reading and writing, but think critically, analyze information and filter digital content. Collaboration between teachers, parents and technology as the main solution to achieve a goal. Integration of technology-based learning will also be an effective means of increasing student literacy. In an increasingly digitized world, this collaborative effort is necessary so that the younger generation can face challenges.